Energy production from municipal solid waste in low to middle income countries: a case study of how to build a circular economy in Abuja, Nigeria - Dickson, Emmanuel Mela; Hastings, Astley; Smith, Jo (Frontiers in Sustainability, 2023)
The volume of municipal solid waste produced in many cities in low to middle income countries exceeds the capacity of handling facilities causing environmental and health risks. This study provides the most comprehensive analysis to date of municipal solid waste management in Abuja, Nigeria. We use existing waste management data from Abuja municipal authorities, integrated with secondary data from the literature. The organic fraction of municipal solid waste from Abuja (7.1×107 (±4×106) kg y-1) has potential to produce 3.6×106 (±2×105) m3 y-1 biogas. This could provide 7.8×103 (±4×102) MWh y-1 electricity, equivalent to 8% of annual electricity requirement, 4.0×107 (±2×106) MJ y-1 heat, and 5.3×105 (±3×104) kg y-1 digestate use as bio-fertilizer. Potential power generation by thermochemical conversion for combined heat and electricity is much greater, 7.73×104 (±4×103) MWh y-1, equivalent to 83% of power requirement, but does not produce bio-fertilizer. Using the organic fraction for anaerobic digestion and the remaining waste for thermochemical conversion provides combined heat and energy that is 91.5% of Abuja power requirements, while also producing digestate. Barriers to implementation include informal waste recyclers with poor collection and handling procedures, absence of public education, weak environmental policies and lack of funding. There is a need for periodic review of policies and waste legislation to create a circular economy in Abuja.